Photoreception in Phytoplankton - Colley, Nansi Jo (Integr Comp Biol, 2016)
In many species of phytoplankton, simple photoreceptors monitor ambient lighting. Photoreceptors provide a number of selective advantages including the ability to assess the time of day for circadian rhythms, seasonal changes, and the detection of excessive light intensities and harmful UV light. Photoreceptors also serve as depth gauges in the water column for behaviors such as diurnal vertical migration. Photoreceptors can be organized together with screening pigment into visible eyespots. In a wide variety of motile phytoplankton, including Chlamydomonas, Volvox, Euglena, and Kryptoperidinium, eyespots are light-sensitive organelles residing within the cell. Eyespots are composed of photoreceptor proteins and typically red to orange carotenoid screening pigments. This association of photosensory pigment with screening pigment allows for detection of light directionality, needed for light-guided behaviors such as positive and negative phototaxis. In Chlamydomonas, the eyespot is located in the chloroplast and Chlamydomonas expresses a number of photosensory pigments including the microbial channelrhodopsins (ChR1 and ChR2). Dinoflagellates are unicellular protists that are ecologically important constituents of the phytoplankton. They display a great deal of diversity in morphology, nutritional modes and symbioses, and can be photosynthetic or heterotrophic, feeding on smaller phytoplankton. Dinoflagellates, such as Kryptoperidinium foliaceum, have eyespots that are used for light-mediated tasks including phototaxis. Dinoflagellates belonging to the family Warnowiaceae have a more elaborate eye. Their eye-organelle, called an ocelloid, is a large, elaborate structure consisting of a focusing lens, highly ordered retinal membranes, and a shield of dark pigment. This complex eye-organelle is similar to multicellular camera eyes, such as our own. Unraveling the molecular makeup, structure and function of dinoflagellate eyes, as well as light-guided behaviors in phytoplankton can inform us about the selective forces that drove evolution in the important steps from light detection to vision. We show here that the evolution from simple photoreception to vision seems to have independently followed identical paths and principles in phytoplankton and animals, significantly strengthening our understanding of this important biological process.